042 Individualised assessment of response to clopidogrel in patients presenting with acute coronary syndromes: a role for short thromboelastography?. (22nd September 2015) - Amoah, V; Worrall, A M; Hobson, A R; Smallwood, A; Rajendra, R; Vickers, J; Nevill, A M; Dunmore, S; Curzen, N; Cotton, J M
Abstract : Introduction: Many centres already use the thrombelastograph (TEG) Haemostasis Analyser to monitor whole blood clotting parameters following cardiothoracic and other surgical procedures. Our group has modified this technique (short TEG, sTEG), to allow the rapid identification of aspirin and clopidogrel hypo-responsiveness. We sought to validate the sTEG area under curve (AUC)15 parameter, in patients admitted with acute coronary syndromes (ACS) by comparing sTEG with the VerifyNow (VN) analyser, and vasodilator-stimulated phosphoprotein (VASP) assay. Methods: Forty-nine patients admitted with ACS and planned for angiography were studied. All had either ECG changes of ischaemia and/or a raised Troponin I. Aspirin and clopidgrel loading were as per contemporary UK practice. Whole blood samples were collected after sheath insertion. The sTEG AUC15 in response to ADP was calculated using a specially developed software programme. Samples were also analysed using the VN (Accumetrics, California, USA) system as per the manufacturers` instructions and VASP assay was performed within 12 h of sampling using a commercial system. The clinical endpoint was adverse clinical events (ACE) at 12 months (death, myocardial infarction (MI), repeat revascularisation (RR), stroke or unplanned cardiovascular hospitalisation (UCH). Results: Of the 49 patients investigated (mean age 63 (39–87), 16 female) successful readings were obtained for sTEG, VN P2Y12 and VASP in 47, 49 and 39 subjects respectively. The mean sTEG AUC15 was 742.1±295.6 mm/min, mean VN platelet response units (PRU) was 235.3±105, and mean VASP platelet reactivity index (PRI) 49.3±20.6%. These three variables were normally distributed. sTEG AUC15 correlated with VN PRU r 2 =0.54, p<0.0001 (Abstract 42 Figure 1a ), with a weaker, but significant correlation seen with VASP PRI r 2 =0.26, p=0.001 (Abstract 42 Figure 1b ). Previous studies have estimated a clinically relevant clopidogrel response cut off point VN PRU of 240. In our study, individuals with a PRU ≥240 had significantly greater mean AUC15 compared to those with <240 (911±195, n=29 vs 493±238, n=19, p=<0.0001) (Abstract 42 Figure 2a ). sTEG AUC15, using a cut off of 800 mm/min (Abstract 42 Figure 2b ) and VN PRU using a cut off of 240 predicted ACE at 1 year (p<0.02). During the follow up period there were 5 (10%) ACE (1 MI, 1 RR, and 3 UCH). Conclusions: This study demonstrates that sTEG, a simple, time responsive technique correlates with VN and VASP methods, and in the studied group identified a cohort of patients with ACE at 1 year. However, further large scale trials of this technique are required to verify this finding.